Regulating triacylglycerol cycling for high-efficiency production of polyunsaturated fatty acids and derivatives - Fei Du; Qing Xu; Xin Li; Yiwen Hang; Duoduo Zhang; Feng Zhang; Wang Ma; Xiaoman Sun; He Huang (Nature Communications)
Abstract Lipid degradation is generally considered an antagonistic pathway to lipid synthesis, so this pathway is often removed to improve lipid production. In this study, triacylglycerol (TAG) cycling formed by lipid degradation is found to be crucial for long-chain polyunsaturated fatty acid (PUFA) biosynthesis; this result contradicts the notion that lipid degradation is a useless process. Specifically, we demonstrate that TAG cycling promoting PUFA biosynthesis occurred in Yarrowia lipolytica and Mortierella alpina via the desaturase/elongase pathway but not in Schizochytrium sp. with the polyketide synthase (PKS) pathway. Exploiting the TAG cycling mechanism, a strategy of decoupling the TAG biosynthesis and degradation is developed. Using this strategy, the titers of C20:5, C22:5 and prostaglandin F2α (PGF2α) in Y. lipolytica are improved by 116.2%, 99.4% and 41.7%, respectively. Our findings highlight the potential of the TAG cycling for related biochemical synthesis in the construction of excellent oleaginous engineered strains.